Hubungan Stres Kerja Fisiologis, Stres Kerja Psikologis dan Stres Kerja Perilaku Dengan Kinerja Karyawan - Ela Nurdiawati; Nina Atiatunnisa (Faletehan Health Journal, 2018)
Employee performance is the result of work achieved by a person or group of people in accordance with the authority or responsibility of each employee during a certain period. Job stress as an adjustment response is mediated by individual differences and psychological processes which are a consequence of any action from outside (environment) of work, a situation that assigns excessive psychological or physical demand to someone. Based on the preliminary study, there were 11 performance reduction data (73%) of them experienced inaccurate work, completed work on time, delays in work, and always violated company rules. This study aims to determine the relationship between job stress both in physiological, psychological and behavioral to employee performance. The subject of research is the worker of production area of PT. Unggul Cipta Serang Technology at 2018 conducted from April to July, this study using Cross-sectional design with a sample size of 60 respondents, the measuring tool used is a questionnaire. This research is tested using univariate test to observe the representation and bivariate (chi-square) to see the relationship. Based on bivariate test, there is a significant correlation between work stress, physiological stress and psychological work stress on employee performance with pv = 0,000, so if job stress, physiological or psychological stress is higher, the worse the worker performance and vice versa. While there is no significant relationship between work stress behavior with employee performance with value pv = 0,169. Therefore, it is important that corporate leaders need to make various efforts to minimize work stress both physiologically, psychologically and behaviorally among workers such as counseling, health clinics and safety sign in the work area.